Human immunoglobulin G antibody response to iron-repressible and other membrane proteins of Porphyromonas (Bacteroides) gingivalis. - Chen, C K (1991)
The human immunoglobulin G (IgG) immune response against Porphyromonas (Bacteroides) gingivalis A7A1-28 iron-repressible membrane proteins (IRMPs) and other membrane proteins was examined by immunoblot analysis. Thirty sera from patients with adult periodontitis and 30 sera from periodontally healthy subjects were included. Iron limitation of P. gingivalis was achieved by growing bacteria in brain heart infusion broth supplemented with protoporphyrin IX and 250 microM alpha, alpha'-dypyridyl, a ferrous iron chelator. Iron-sufficient growth was achieved by growing bacteria in the same medium without alpha, alpha'-dypyridyl. Human sera, in particular those from patients with periodontitis who exhibited high levels of IgG against whole cells of P. gingivalis A7A1-28 in serum in an enzyme-linked immunosorbent assay (ELISA), commonly reacted with five membrane proteins with apparent molecular masses of 80, 67.5, 51, 40.5, and 28 kDa and four IRMPs of 46, 43, 37.5, and 22 kDa. More than 80% of the sera from patients with periodontitis and high levels of IgG against strain A7A1-28 in serum by ELISA reacted with the 46-, 43-, and 37.5-kDa IRMPs, and 40% of these subjects expressed immunoreactivity against the 22-kDa IRMP. Sera from patients with periodontitis and low levels of IgG against strain A7A1-28 in serum by ELISA and sera from periodontally healthy subjects exhibited less immunoreactivity against IRMPs and the five membrane proteins of P. gingivalis. The present study indicates that P. gingivalis IRMPs are immunogenic and that these proteins are expressed in vivo.